An economic analysis of winter vegetables production in some selected areas of Narsingdi district - Akter, S; Islam, MS; Rahman, MS (Journal of the Bangladesh Agricultural University, 2012)
The present study was designed to assess the comparative profitability of selected winter vegetables: namely tomato, cauliflower and cabbage. In total, 90 farmers (30 each growing tomato, cauliflower and cabbage) were randomly selected from two villages under Shibpur Upazila in Narsingdi district. Both tabular and quantitative analyses were done to achieve the major objectives of the study. The major findings of the study revealed that production of all the selected vegetables were profitable. The per hectare gross cost of production of tomato, cauliflower and cabbage were Tk. 118000, 116977 and 120522, respectively and the corresponding gross returns were Tk. 217020, 210000 and 220000, respectively. The per hectare net returns of producing tomato, cauliflower and cabbage were Tk. 97000, 93023 and 99478, respectively. In other words, all the selected winter vegetables were highly profitable to the farmers. However, the farmers earned the highest profit from cabbage. The revenue type Cobb-Douglas production function analysis indicated that per hectare gross returns were significantly influenced by the use of human labour, tillage, seeds, fertilizers, irrigation and insecticides. These factors were directly or jointly responsible for influencing the per hectare gross returns of tomato, cauliflower and cabbage. The study reported some problems and constraints which are related to production and marketing of these vegetables. Based on the findings of the study, some recommendations were made to improve cultural and management practices for selected winter vegetables farming with a view to increase the income and employment opportunities of the farmers. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11036 J. Bangladesh Agril. Univ. 9(2): 241246, 2011